2015
DOI: 10.1186/s40563-015-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibre reinforced polymers in the rehabilitation of damaged masonry wallettes

Abstract: In the past decade, the interest in repair and retrofitting of existing structures and rehabilitation of the damaged structures has led to the development of more effective and low invasive architectural and engineering strategies. In this aspect, the application of fibre reinforced polymer (FRP) strengthening techniques has become reasonably widespread as suitable solutions in addition to the traditional ones. They are promising techniques because of their key characteristics such as: high specific strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…ElGawady et al [19] found that the lateral strength and stiffness of a masonry wall was 1.4-5.9 times higher after retrofitting using a one-sided carbon fiber-reinforced polymer (CFRP) bonding method. Chagas et al [20] reinforced a masonry wall with vertical glass fiber-reinforced polymer (GFRP) strips. Similar studies on the cyclic loading of brick walls strengthened with vertical, horizontal, or diagonal CFRP strips or basalt fiber-reinforced polymer (BFRP) strips were conducted by Fam et al [21], Marcari et al [22], and Zhou et al [23,24].…”
Section: ) Frp Retrofitting Techniquementioning
confidence: 99%
“…ElGawady et al [19] found that the lateral strength and stiffness of a masonry wall was 1.4-5.9 times higher after retrofitting using a one-sided carbon fiber-reinforced polymer (CFRP) bonding method. Chagas et al [20] reinforced a masonry wall with vertical glass fiber-reinforced polymer (GFRP) strips. Similar studies on the cyclic loading of brick walls strengthened with vertical, horizontal, or diagonal CFRP strips or basalt fiber-reinforced polymer (BFRP) strips were conducted by Fam et al [21], Marcari et al [22], and Zhou et al [23,24].…”
Section: ) Frp Retrofitting Techniquementioning
confidence: 99%